Perlindungan Hukum Terhadap Korban Glorifikasi dari Pelaku Tindak Pidana Pencabulan - Tjok Istri Agung Mellynia Putri Saraswati; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2022)
Today, children are often victims of sexual abuse. Child molestation is a very disgraceful treatment that damages the future of the child, both physically and psychologically. One of the examples of cases of child abuse is the case that was committed by SJ. After being released from prison, SJ received a lot of applause in the public. The glorification of the SJ case can be seen as normalizing perpetrators of sexual abuse in the public. The purpose of this research is to examine the legal arrangements for the glorification of perpetrators of criminal acts of obscenity and to reveal protection for victims who have experienced crimes of sexual abuse. The type of research used is normative legal research with a statutory approach. Sources of legal materials are primary and secondary legal materials. To get valid data, the researcher used library research techniques, namely taking notes, summarizing, and giving reviews. The results of the study revealed that the regulation of perpetrators of criminal acts of obscenity is regulated in Article 289 of the Criminal Code and for the glorification of perpetrators of criminal acts of obscenity has not been specifically regulated. Protection of victims who have experienced criminal acts of obscenity is regulated in Articles 6, 7 and 7A of Law no. 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. ban Glorifikasi Dari Pelaku Tindak Pidana Pencabulan